Phytochemical Studies And Cytotoxicity Assessment Of Stem Bark Extracts From Calophyllum Macrocarpum Hook. F. And Calophyllum Recurvatum P. F. Stevens - Firouz, Noor Syarafana (2024)
Numerous Calophyllum sp. have long been valued widely in Asian traditional medicine especially in Malaysia. The modern natural product-based research on the genus Calophyllum has further revealed a variety of biological functions exhibited by these plants, such as inhibition of HIV, antioxidant, and cytotoxicity. Species from the genus Calophyllum are also abundant in phenolic compounds especially xanthones and coumarins. However, Calophyllum macrocarpum and Calophyllum recurvatum are among the species that still need more scientific documentation on the phytochemistry and pharmacological aspects. In this research project, the stem bark of Calophyllum macrocarpum and Calophyllum recurvatum were being subjected for phytochemical investigation, which led to the isolation of various phytochemicals such as xanthones and coumarins. Extensive chromatographic separations and purifications on the stem bark of C. macrocarpum (n-hexane and chloroform extracts) resulted in isolation of prenylated xanthones; ananixanthone (1), trapezifolixanthone (2), 8-deoxygartanin (3), as well as triterpenoid; stigmasterol (4) and friedelin (5). Furthermore, thwaitesixanthone (6), teysmanone A (7), soulattrolide (8), calanone (9), as well as friedelin (5) were successfully being isolated from the stem bark of C. recurvatum (n-hexane and chloroform extracts).